Aluminum-seawater battery anode alloy material and preparation method and application thereof

By adding alloy elements such as Mg, Sn, In and Zn to the aluminum-seawater battery anode material, and through solid solution treatment and hot rolling processes, an aluminum-seawater battery anode alloy material with excellent electrochemical activity and corrosion resistance is prepared. , which solves the problems of insufficient electrochemical activity and corrosion resistance of existing materials.

CN119340409APending Publication Date: 2025-01-21HARBIN ENG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411616851.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing aluminum-seawater battery anode materials have insufficient electrochemical activity and corrosion resistance in seawater media, resulting in the forward movement of the open circuit potential and the slowing of activation rate, affecting the discharge efficiency.

Method used

Aluminum-seawater battery anode alloy material is used, its composition includes Mg 0.8~1.5%, Sn 0.25~0.4%, In 0.3~0.35%, Zn 0~2.7% and the balance Al, through smelting, solution treatment and hot rolling It is prepared by other processes to improve the electrochemical activity and corrosion resistance of the material.

Benefits of technology

The excellent electrochemical activity and corrosion resistance of the aluminum-seawater battery anode material in seawater medium is achieved. The open circuit voltage is -1.31~-1.09V and the corrosion current is 1.18~7.93μA/cm2, which significantly improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340409A_ABST
    Figure CN119340409A_ABST
Patent Text Reader

Abstract

The invention provides an aluminum-seawater battery anode alloy material as well as a preparation method and application thereof, and belongs to the field of metal fuel cells. The aluminum-seawater battery anode alloy material provided by the invention is prepared from the following elements in percentage by mass: 0.8 to 1.5 percent of Mg, 0.25 to 0.4 percent of Sn, 0.3 to 0.35 percent of In, 0 to 2.7 percent of Zn and the balance of Al. The result of the embodiment shows that the open-circuit voltage of the aluminum-seawater battery anode alloy material provided by the invention in 3.5 wt% NaCl electrolyte is-1.31 to-1.09 V, the corrosion current is 1.18 to 7.93 mu A / cm < 2 >, and the aluminum-seawater battery anode alloy material has good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal fuel cells, and in particular to an aluminum-seawater battery anode alloy material and a preparation method and application thereof. Background Art

[0002] Aluminum-seawater battery is a chemical battery with aluminum as anode material, seawater as electrolyte, and low hydrogen evolution overpotential metal (such as nanotube nickel) as cathode material. The battery only consumes aluminum and seawater during the reaction process, and converts chemical energy into electrical energy through the redox reaction between aluminum and seawater. In the aluminum fuel cell energy storage system, its reaction principle is different from that of traditional aluminum-air batteries. No additional air is required, and the reaction can be carried out in an oxygen-free environment such as underwater. When the aluminum-seawater battery is not working, it can be stored dry for a long time. When working, it only needs to pass seawater into the battery to activate it. The seawater electrolyte can be replenished / discharged at any time according to the working time. The products are H2 and Al(OH)3. The reaction products can be recycled and have no pollution to the environment, meeting the needs of underwater equipment for new energy systems.

[0003] Aluminum metal is the most abundant metal element in the earth's crust. Industrial pure aluminum contains impurity elements such as Fe, Si, and Cu. The presence of impurity elements will accelerate the corrosion of the aluminum anode in the electrolyte. In addition, the aluminum anode will spontaneously form a dense aluminum oxide film in the electrolyte. The presence of the oxide film will cause the aluminum anode potential to move forward and the activation rate to slow down. The presence of impurities and oxide film will also greatly affect the discharge efficiency.

[0004] At present, the method to reduce the corrosion of aluminum anode and improve its activity is to alloy aluminum and add metal elements with high activity, high hydrogen evolution overpotential and low melting point, such as Mg, Mn, In, Sn, Ga, Zn, Bi, Ce, etc. For example, an aluminum alloy anode material for battery, the composition and mass percentage of the aluminum alloy anode material are: Mg: 0.5-1.0%; Ga: 0.1-1.0%; Bi: 0.5-1.0%; Ce: 0.05-0.8%; Pb: 0.005-1.0%; Ca: 0.005-0.05%; the balance is Al. Although the aluminum alloy anode material for battery has the advantage of high electrochemical performance, its relatively negative open circuit potential is only achieved when using alkaline electrolyte (3.5% NaCl + 25% NaOH), and the open circuit potential in 3.5% NaCl aqueous solution is positive. Summary of the invention

[0005] The purpose of the present invention is to provide an aluminum-seawater battery anode alloy material and a preparation method and application thereof. The aluminum-seawater battery anode alloy material provided by the present invention has excellent electrochemical activity and corrosion resistance in seawater medium.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The invention provides an aluminum-seawater battery anode alloy material, which is composed of the following elements by mass percentage: 0.8-1.5% Mg, 0.25-0.4% Sn, 0.3-0.35% In, 0-2.7% Zn and the balance Al.

[0008] Preferably, it is composed of the following elements: Mg 0.9-1.5%, Sn 0.25-0.35%, In 0.32-0.35%, Zn 1-2.7% and the balance Al.

[0009] Preferably, it is composed of the following elements: Mg 1.2-1.5%, Sn 0.25-0.3%, In 0.34-0.35%, Zn 2-2.7% and the balance Al

[0010] The present invention provides a method for preparing the aluminum-seawater battery anode alloy material described in the above technical solution, comprising the following steps:

[0011] (1) melting the alloy raw materials and then casting to obtain an aluminum ingot;

[0012] (2) subjecting the aluminum ingot obtained in step (1) to a solid solution treatment to obtain a solid solution aluminum ingot;

[0013] (3) hot rolling the solid solution aluminum ingot obtained in step (2) to obtain an aluminum-seawater battery anode alloy material.

[0014] Preferably, the temperature of the solution treatment in step (2) is 420-500° C., and the holding time of the solution treatment is 8-10 h.

[0015] Preferably, the initial rolling temperature of the hot rolling in step (3) is 290-310°C.

[0016] Preferably, the total pressing amount of hot rolling in step (3) is 60-70%; and the number of hot rolling passes is 3-4 times.

[0017] Preferably, during the hot rolling, the pressing amount of the first pass is 25-30%, and the pressing amounts of the remaining passes are independently 10-20%.

[0018] Preferably, in step (3), preheating is performed before hot rolling, the preheating temperature is 290-310° C., and the preheating holding time is 10-15 min.

[0019] The present invention provides the application of the aluminum-seawater battery anode alloy material described in the above technical scheme or the aluminum-seawater battery anode alloy material prepared by the preparation method described in the above technical scheme in aluminum-seawater battery anode and aluminum-seawater battery.

[0020] The invention provides an aluminum-seawater battery anode alloy material, which comprises, by mass percentage, 0.8-1.5% Mg, 0.25-0.4% Sn, 0.3-0.35% In, 0-2.7% Zn and the balance Al. The invention can improve discharge activity and reduce hydrogen evolution corrosion rate by adding alloy element Mg, and at the same time, adjust the content of Mg element to form trace Mg2Al3 with Al, and the trace Mg2Al3 can play a role in refining grains and improving mechanical properties of materials; alloy element Sn can form a low-temperature eutectic with In, promote the rupture of Al2O3 passivation film, inhibit the growth of oxide film, and improve the electrochemical activity of aluminum anode; alloy element Zn can play a role in refining grains and reducing alloy defects, and at the same time, Zn can promote Al-In alloying, reduce the polarization of aluminum anode, make the electrode potential more negative, and further improve the electrochemical activity and corrosion resistance of aluminum-seawater battery anode alloy material. The results of the embodiment show that the open circuit voltage of the aluminum-seawater battery anode alloy material provided by the present invention in a 3.5wt% NaCl electrolyte is -1.31 to -1.09V, and the corrosion current is 1.18 to 7.93μA / cm 2 , with good electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The open circuit potential diagrams of the aluminum-seawater battery anode alloy materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0022] The invention provides an aluminum-seawater battery anode alloy material, which is composed of the following elements by mass percentage: 0.8-1.5% Mg, 0.25-0.4% Sn, 0.3-0.35% In, 0-2.7% Zn and the balance Al.

[0023] In terms of mass percentage, the aluminum-seawater battery anode alloy material provided by the present invention includes Mg0.8-1.5%, preferably 0.9-1.5%, and more preferably 1.2-1.5%. In the present invention, Mg can improve discharge activity and reduce hydrogen evolution corrosion rate. The present invention controls the content of Mg element within the above range to improve the electrochemical activity and corrosion resistance of the aluminum-seawater battery anode alloy material. At the same time, the Mg element can also form trace Mg2Al3 with Al, and trace Mg2Al3 can play a role in refining grains and improving the mechanical properties of the material.

[0024] The aluminum-seawater battery anode alloy material provided by the present invention includes Sn0.25-0.4%, preferably 0.25-0.35%, and more preferably 0.25-0.3%, by mass percentage. In the present invention, Sn can form a low-temperature eutectic with In, promote the rupture of the Al2O3 passivation film, inhibit the growth of the oxide film, and improve the electrochemical activity of the aluminum anode. The present invention controls the content of the Sn element to be within the above range so that it can cooperate with the In element to improve the electrochemical activity of the aluminum anode.

[0025] The aluminum-seawater battery anode alloy material provided by the present invention includes 0.3-0.35% In by mass percentage, preferably 0.32-0.35%, and more preferably 0.34-0.35%. In the present invention, In can promote the activation of the aluminum anode and reduce the corrosion rate. In can form a low-temperature eutectic with Sn, promote the rupture of the Al2O3 passivation film, inhibit the growth of the oxide film, and improve the electrochemical activity of the aluminum anode. The present invention controls the content of the In element to be within the above range so that it can cooperate with the Sn element to improve the electrochemical activity of the aluminum anode.

[0026] In terms of mass percentage, the aluminum-seawater battery anode alloy material provided by the present invention includes 0 to 2.7% Zn, preferably 1 to 2.7%, more preferably 2 to 2.7%, and further preferably 2.5 to 2.7%. In the present invention, Zn can refine the grains and reduce alloy defects. At the same time, Zn can promote Al-In alloying, reduce the polarization of the aluminum anode, make the electrode potential more negative, and further improve the electrochemical properties of the aluminum-seawater battery anode alloy material. The present invention controls the content of the Zn element within the above range to improve the electrochemical activity and corrosion resistance of the aluminum-seawater battery anode alloy material.

[0027] The aluminum-seawater battery anode alloy material provided by the present invention can improve discharge activity and reduce hydrogen evolution corrosion rate by adding alloy element Mg, and at the same time, the Mg element content can be adjusted to form a trace amount of Mg2Al3 with Al, and the trace amount of Mg2Al3 can play a role in refining grains and improving material mechanical properties; the alloy element Sn can form a low-temperature eutectic with In, promote the rupture of Al2O3 passivation film, inhibit the growth of oxide film, and improve the electrochemical activity of aluminum anode; the alloy element Zn can play a role in refining grains and reducing alloy defects, and at the same time, Zn can promote Al-In alloying, reduce the polarization of the aluminum anode, make the electrode potential more negative, and further improve the electrochemical activity and corrosion resistance of the aluminum-seawater battery anode alloy material.

[0028] The present invention provides a method for preparing the aluminum-seawater battery anode alloy material described in the above technical solution, comprising the following steps:

[0029] (1) melting the alloy raw materials and then casting to obtain an aluminum ingot;

[0030] (2) subjecting the aluminum ingot obtained in step (1) to a solid solution treatment to obtain a solid solution aluminum ingot;

[0031] (3) hot rolling the solid solution aluminum ingot obtained in step (2) to obtain an aluminum-seawater battery anode alloy material.

[0032] The invention melts the alloy raw material and then casts it to obtain the aluminum ingot.

[0033] In the present invention, the alloy raw materials are preferably aluminum particles with a purity of ≥99.99%, tin particles with a purity of ≥99.99%, indium particles with a purity of ≥99.995%, zinc particles with a purity of ≥99.995%, and magnesium particles with a purity of ≥99.99%. The present invention has no special requirements on the particle size of aluminum particles, tin particles, indium particles, zinc particles, and magnesium particles, as long as they can be placed in the crucible. The present invention limits the type and purity of the alloy raw materials to the above range to reduce impurities in the alloy.

[0034] In the present invention, the order of adding the alloy raw materials is preferably: first add aluminum to melt, then add tin, indium and zinc, and then add magnesium after the tin, indium and zinc are melted.

[0035] In the present invention, the tin, indium, zinc and magnesium are preferably wrapped with aluminum foil before adding. In the present invention, the tin, indium, zinc and magnesium are wrapped with aluminum foil before adding, which can reduce the oxidation of active metals such as magnesium and improve the utilization rate.

[0036] In the present invention, the smelting is preferably carried out in an inert atmosphere; the equipment used for the smelting is preferably a vacuum melting furnace; the vacuum degree of the vacuum melting furnace is preferably 0.5-0.7 Pa; and the inert atmosphere is preferably argon.

[0037] In the present invention, the specific steps of smelting are preferably: placing aluminum particles in a crucible, evacuating the crucible, filling it with inert gas and heating it to a first melting temperature for a first insulation, then adding tin particles, indium particles and zinc particles wrapped in aluminum foil at the first melting temperature for a second insulation, and finally cooling it to the second melting temperature and adding magnesium particles wrapped in aluminum foil for a third insulation.

[0038] In the present invention, the heating rate of the temperature rise to the first melting temperature is preferably 8-12°C / min, more preferably 10°C / min; the first melting temperature is preferably 730-760°C; the first heat preservation time is preferably 1-1.5h; the second heat preservation time is preferably 10-20min; the second melting temperature is preferably 710-730°C; the third heat preservation time is preferably 7-10min. The present invention sets the parameters of the smelting process within the above range to make the alloy raw materials more fully mixed and uniform.

[0039] In the present invention, electromagnetic stirring is preferably performed during the third heat preservation process. The present invention has no special requirements on the speed of electromagnetic stirring, and stirring can be performed using a speed commonly used by those skilled in the art. In the present invention, electromagnetic stirring during the third heat preservation process can promote uniform mixing of the alloy melt.

[0040] In the present invention, after the third heat preservation is completed, the molten alloy is preferably allowed to stand at 710-730°C; the molten alloy is preferably allowed to stand for 5-10 minutes, more preferably for 5-8 minutes. In the present invention, the unmelted metal or impurities in the hot melt are precipitated by standing the molten alloy, thereby improving the quality and purity of the finished aluminum alloy.

[0041] In the present invention, after the standing is completed, the hot melt obtained by the standing is preferably cast to obtain an aluminum ingot.

[0042] In the present invention, the specific operation of the casting is preferably: pouring the hot melt into a mold preheated to 200° C. and naturally cooling in the air to form the mold.

[0043] After obtaining the aluminum ingot, the present invention performs a solid solution treatment on the aluminum ingot to obtain a solid solution aluminum ingot.

[0044] In the present invention, the solution treatment is preferably carried out in a muffle furnace; the temperature of the solution treatment is preferably 420-500°C, more preferably 450°C; the holding time of the solution treatment is preferably 8-10h, more preferably 9-10h. In the present invention, the heating rate to the solution temperature is preferably 10-15°C / min. The present invention limits the temperature and time of the solution treatment to the above range to improve the plasticity and toughness of the alloy and prevent the aluminum alloy from cracking during subsequent rolling; the second phase in the alloy can be completely or maximally dissolved into the solid solution, thereby improving the corrosion resistance of the material.

[0045] In the present invention, the cooling method of the solution treatment is preferably water cooling.

[0046] After obtaining the solid solution aluminum ingot, the present invention hot rolls the solid solution aluminum ingot to obtain the aluminum-seawater battery anode alloy material.

[0047] In the present invention, preheating is preferably performed before hot rolling; the preheating temperature is preferably 290-310°C, more preferably 300°C; the preheating holding time is preferably 10-15 minutes, more preferably 12-14 minutes. In the present invention, limiting the preheating temperature and time to the above range can eliminate stress in the material and avoid cracking of the material during rolling.

[0048] The present invention preferably cuts the solid solution aluminum ingot into aluminum sheets before preheating; the cutting is preferably wire cutting; the thickness of the aluminum sheet is preferably 2.4 to 2.6 mm. The present invention limits the thickness of the aluminum sheet to the above range to facilitate hot rolling.

[0049] In the present invention, the initial rolling temperature of the hot rolling is preferably 290-310°C, more preferably 300°C; the total pressing amount of the hot rolling is preferably 60-70%, more preferably 65-70%; the number of hot rolling passes is preferably 3-4 times, more preferably 3 times. In the present invention, the pressing amount of the first pass of the hot rolling is preferably 25-30%, and the pressing amounts of the remaining passes are independently preferably 10-20%. The present invention limits the initial rolling temperature of the hot rolling and the pressing amount of each pass to the above ranges to avoid material cracking during the rolling process.

[0050] The present invention can improve the plasticity and toughness of the alloy, reduce defects in the alloy material, prevent the aluminum alloy from cracking during subsequent rolling, ensure that the alloy has good corrosion resistance, and further improve the electrochemical properties of the anode alloy material by performing solid solution treatment and hot rolling on the anode alloy material.

[0051] The present invention also provides the use of the aluminum-seawater battery anode alloy material described in the above technical solution or the aluminum-seawater battery anode alloy material prepared by the preparation method described in the above technical solution in aluminum-seawater battery anode and aluminum-seawater battery.

[0052] The present invention has no special limitation on the size of the aluminum-seawater battery anode, and the aluminum-seawater battery anode alloy material can be cut to a corresponding size as required.

[0053] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] An aluminum-seawater battery anode alloy material, composed of the following elements by mass percentage: 0.8% Mg, 0.4% Sn, 0.3% In and the balance Al;

[0056] The method for preparing the aluminum-seawater battery anode alloy material comprises the following steps:

[0057] (1) Weighing aluminum particles, aluminum foil, magnesium particles, tin particles and indium particles, wrapping the weighed magnesium particles, tin particles and indium particles with aluminum foil and placing them in a silo of a vacuum melting furnace, placing aluminum particles in a crucible, evacuating and maintaining the vacuum degree at 0.667 Pa, then introducing argon gas, heating to 730°C at a heating rate of 10°C / min under an Ar atmosphere, and then keeping the temperature for 1 hour, then adding tin particles and indium particles wrapped in aluminum foil at 730°C and keeping the temperature for 10 minutes, finally cooling to 710°C, adding magnesium particles wrapped in aluminum foil, and simultaneously turning on electromagnetic stirring, keeping the temperature for 7 minutes under stirring conditions, and then standing at 710°C for 5 minutes to obtain a hot melt, pouring the hot melt into a mold preheated to 200°C, and naturally cooling and forming in air to obtain an aluminum ingot;

[0058] (2) subjecting the aluminum ingot obtained in step (1) to a solid solution treatment at 450° C. for 10 hours and then water cooling to obtain a solid solution aluminum ingot;

[0059] (3) The solid solution aluminum ingot obtained in step (2) is wire-cut to obtain a 2.5 mm thick aluminum sheet, the aluminum sheet is placed in a muffle furnace, the muffle furnace is heated to 300° C., the muffle furnace is kept warm for 15 minutes for preheating, and then hot-rolled to obtain an aluminum-seawater battery anode alloy material; the total pressing amount of the hot rolling is 65%; the number of hot rolling passes is 3 times; the pressing amount of the first pass during the hot rolling is 30%, the pressing amount of the second pass is 20%, and the pressing amount of the third pass is 15%.

[0060] Example 2

[0061] An aluminum-seawater battery anode alloy material, composed of the following elements by mass percentage: 1.2% Mg, 0.25% Sn, 0.35% In and the balance Al;

[0062] The method for preparing the aluminum-seawater battery anode alloy material comprises the following steps:

[0063] (1) Weighing aluminum particles, aluminum foil, magnesium particles, tin particles and indium particles, wrapping the weighed magnesium particles, tin particles and indium particles with aluminum foil and placing them in a silo of a vacuum melting furnace, placing aluminum particles in a crucible, evacuating and maintaining the vacuum degree at 0.667 Pa, then introducing argon gas, heating to 730°C at a heating rate of 10°C / min under an Ar atmosphere, and then keeping the temperature for 1 hour, then adding tin particles and indium particles wrapped in aluminum foil at 730°C and keeping the temperature for 10 minutes, finally cooling to 710°C, adding magnesium particles wrapped in aluminum foil, and simultaneously turning on electromagnetic stirring, keeping the temperature for 7 minutes under stirring conditions, and then standing at 710°C for 5 minutes to obtain a hot melt, pouring the hot melt into a mold preheated to 200°C, and naturally cooling and forming in air to obtain an aluminum ingot;

[0064] (2) subjecting the aluminum ingot obtained in step (1) to a solid solution treatment at 450° C. for 10 hours and then water cooling to obtain a solid solution aluminum ingot;

[0065] (3) The solid solution aluminum ingot obtained in step (2) is wire-cut to obtain a 2.5 mm thick aluminum sheet, the aluminum sheet is placed in a muffle furnace, the muffle furnace is heated to 300° C., the muffle furnace is kept warm for 15 minutes for preheating, and then hot-rolled to obtain an aluminum-seawater battery anode alloy material; the total pressing amount of the hot rolling is 65%; the number of hot rolling passes is 3 times; the pressing amount of the first pass during the hot rolling is 30%, the pressing amount of the second pass is 20%, and the pressing amount of the third pass is 15%.

[0066] Example 3

[0067] An aluminum-seawater battery anode alloy material, composed of the following elements by mass percentage: 1.5% Mg, 0.25% Sn, 0.35% In, 2.7% Zn and the balance Al;

[0068] The method for preparing the aluminum-seawater battery anode alloy material comprises the following steps:

[0069] (1) Weighing aluminum particles, aluminum foil, magnesium particles, tin particles, indium particles and zinc particles, wrapping the weighed magnesium particles, tin particles, indium particles and zinc particles with aluminum foil and placing them in a vacuum melting furnace silo, placing aluminum particles in a crucible, introducing argon gas, evacuating and maintaining the vacuum degree at 0.667 Pa under Ar atmosphere, heating to 730°C at a heating rate of 10°C / min and keeping the temperature for 1h, then adding tin particles, indium particles and zinc particles wrapped in aluminum foil at 730°C and keeping the temperature for 10min, finally cooling to 710°C and adding magnesium particles wrapped in aluminum foil, turning on electromagnetic stirring at the same time, keeping the temperature for 7min under stirring conditions, and standing at 710°C for 5min to obtain a hot melt, pouring the hot melt into a mold preheated to 200°C, and naturally cooling and forming in air to obtain an aluminum ingot;

[0070] (2) subjecting the aluminum ingot obtained in step (1) to a solid solution treatment at 450° C. for 10 hours and then water cooling to obtain a solid solution aluminum ingot;

[0071] (3) The solid solution aluminum ingot obtained in step (2) is wire-cut to obtain a 2.5 mm thick aluminum sheet, the aluminum sheet is placed in a muffle furnace, the muffle furnace is heated to 300° C., the muffle furnace is kept warm for 15 minutes for preheating, and then hot-rolled to obtain an aluminum-seawater battery anode alloy material; the total pressing amount of the hot rolling is 65%; the number of hot rolling passes is 3 times; the pressing amount of the first pass during the hot rolling is 30%, the pressing amount of the second pass is 20%, and the pressing amount of the third pass is 15%.

[0072] Comparative Example 1

[0073] A high-purity aluminum alloy (Al 99.99%) is used as the anode alloy material of the aluminum-seawater battery.

[0074] Comparative Example 2

[0075] 1060 commercial aluminum alloy (Fe≤0.35%, Mn≤0.1%, Si≤0.25%, Sb≤0.05%, Cu≤0.15%, Mg≤0.05%, Ti≤0.03%, V≤0.05%, Al≥99.6%) is used as the anode alloy material of aluminum-seawater battery.

[0076] Comparative Example 3

[0077] 5052 commercial aluminum alloy (Si≤0.25%, Cu≤0.1%, Mg 2.2-2.8%, Zn≤0.1%, Mn≤0.1%, Cr 0.15-0.35%, Fe≤0.4%, Al balance) is used as the anode alloy material of aluminum-seawater battery.

[0078] The electrochemical performance of the aluminum-seawater battery anode alloy materials in Examples 1 to 3 and Comparative Examples 1 to 3 was tested using a CS2350M electrochemical workstation. The scanning time was 3600 seconds. A three-electrode system was used. The reference electrode was a saturated calomel electrode, the counter electrode was a platinum electrode, and the active area of ​​the aluminum anode sample was 1 cm 2 The electrolyte was a 3.5 wt% NaCl aqueous solution, and the test temperature was 25 °C.

[0079] The open circuit potential diagrams of the aluminum-seawater battery anode alloy materials of Examples 1 to 3 and Comparative Examples 1 to 3 are as follows: Figure 1 As shown, from Figure 1 It can be seen that the open circuit voltage range of Examples 1 to 3 is -1.31 to -1.09 V, and the stable open circuit voltage of Comparative Examples 1 to 3 is about -0.83 to -0.73 V. The open circuit voltage of Examples 1 to 3 is significantly negatively shifted compared with Comparative Examples 1 to 3. The more negative the open circuit potential, the better the electrochemical performance of the aluminum anode material.

[0080] The corrosion current data of the aluminum-seawater battery anode alloy materials of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.

[0081] Table 1 Corrosion current data of aluminum-seawater battery anode alloy materials of Examples 1 to 3 and Comparative Examples 1 to 3

[0082]

[0083]

[0084] from Figure 1As can be seen from Table 1, compared with Comparative Examples 1 to 3, the corrosion currents of Examples 1 to 3 are lower than those of the Comparative Examples, the corrosion currents are smaller, and the open circuit potentials are negatively shifted. Therefore, the embodiments not only improve the corrosion resistance of the aluminum-seawater battery anode alloy material, but also make the anode have better electrochemical activity.

[0085] The aluminum-seawater battery anode alloy material provided by the present invention has an open circuit voltage of -1.31 to -1.09V in a 3.5wt% NaCl electrolyte and a corrosion current of 1.18 to 7.93μA / cm 2 Compared with the aluminum alloy materials in the prior art, it has a more negative open circuit potential and a smaller corrosion current and has good electrochemical properties.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An aluminum-seawater battery anode alloy material, composed of the following elements by mass percentage: Mg 0.8-1.5%, Sn 0.25-0.4%, In 0.3%-0.35%, Zn 0%-2.7% and the balance Al.

2. The aluminum-seawater battery anode alloy material according to claim 1, characterized in that: It is composed of the following elements: Mg 0.9-1.5%, Sn 0.25-0.35%, In 0.32%-0.35%, Zn 1%-2.7% and the balance Al.

3. The aluminum-seawater battery anode alloy material according to claim 1, characterized in that: It is composed of the following elements: Mg 1.2-1.5%, Sn 0.25-0.3%, In 0.34-0.35%, Zn 2-2.7% and the balance Al.

4. The method for preparing the aluminum-seawater battery anode alloy material according to any one of claims 1 to 3, comprising the following steps: (1) melting the alloy raw materials and then casting to obtain an aluminum ingot; (2) subjecting the aluminum ingot obtained in step (1) to a solid solution treatment to obtain a solid solution aluminum ingot; (3) hot rolling the solid solution aluminum ingot obtained in step (2) to obtain an aluminum-seawater battery anode alloy material.

5. The preparation method according to claim 4, characterized in that: The temperature of the solution treatment in step (2) is 420-500° C., and the holding time of the solution treatment is 8-10 hours.

6. The preparation method according to claim 4, characterized in that: The initial rolling temperature of the hot rolling in step (3) is 290-310°C.

7. The preparation method according to claim 4 or 6, characterized in that: The total pressing amount of hot rolling in step (3) is 60-70%; the number of hot rolling passes is 3-4 times.

8. The preparation method according to claim 7, characterized in that: During the hot rolling, the pressing amount of the first pass is 25-30%, and the pressing amounts of the remaining passes are independently 10-20%.

9. The preparation method according to claim 4, characterized in that: In the step (3), preheating is also performed before hot rolling. The preheating temperature is 290 to 310° C. and the preheating holding time is 10 to 15 minutes.

10. Use of the aluminum-seawater battery anode alloy material according to any one of claims 1 to 3 or the aluminum-seawater battery anode alloy material prepared by the preparation method according to any one of claims 4 to 9 in aluminum-seawater battery anodes and aluminum-seawater batteries.